The role of home pocket garden to achieve quality of life during the pandemic era - Sanusi, Aliyah Nur Zafirah; Abdullah, Fadzidah; Othman, Rosniza; Azmin, Aida Kesuma; Yusof, Zeenat Begam; Asif, Nayeem (e-IPH Ltd UK, 2021)
Before the pandemic, residents in the Klang Valley tend to prioritize indoor living space to outdoor. This study analyzed the importance of outdoor green space in residential buildings. It consists of two objectives; to identify the type of home pocket gardens used and to evaluate the significant impact of home pocket gardens on the quality of life (QOL) during the pandemic. A survey was conducted using a five-point Likert scale and distributed to three housing communities within the Klang Valley. The finding shows the positive role of the Home Pocket Garden on the Quality of Life during the pandemic.